1999
DOI: 10.1109/8.761064
|View full text |Cite
|
Sign up to set email alerts
|

Improved models for long-term prediction of tropospheric scintillation on slant paths

Abstract: The prediction models for tropospheric scintillation on earth-satellite paths from Karasawa, Yamada, and Allnutt and ITU-R are compared with measurement results from satellite links in Europe, the United States, and Japan at frequencies from 7 to 30 GHz and elevation angles of 3 to 33. The existing prediction models relate the long-term average scintillation intensity to the wet term of refractivity at ground level. The comparison shows that the seasonal variation of scintillation intensity is well predicted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 15 publications
0
26
0
4
Order By: Relevance
“…Various statistical models exist for the prediction of the Complementary Cumulative Distribution Function (CCDF) of scintillation intensity (dB) and variance (dB 2 ), using temperature and/or humidity at ground level [1][2][3][4][5][6], profiles [7] or information about clouds [8]. Various measurements have been performed during Olympus and Italsat campaigns in Europe and as well as during other propagation campaigns in tropical climate [9] [10].…”
Section: Measurementsmentioning
confidence: 99%
“…Various statistical models exist for the prediction of the Complementary Cumulative Distribution Function (CCDF) of scintillation intensity (dB) and variance (dB 2 ), using temperature and/or humidity at ground level [1][2][3][4][5][6], profiles [7] or information about clouds [8]. Various measurements have been performed during Olympus and Italsat campaigns in Europe and as well as during other propagation campaigns in tropical climate [9] [10].…”
Section: Measurementsmentioning
confidence: 99%
“…Up to now, it has been demonstrated that turbulence-induced scintillation appears either when strong refractive index inhomogeneities occur or in fair weather cumulus. Recent studies have shown that scintillation effect grows with increasing humidity [14] and increasing integrated water content in heavy clouds [15]. Unlike scintillation, oxygen attenuation is present all the time and is not subject to significant variations.…”
Section: Propagation Impairments and Mitigationmentioning
confidence: 99%
“…The van de Kamp models [19,27] are all based on the observation that scintillation is at least partly associated with the presence along the path of heavy cloud. In the first model (Kamp I), the mean water content, W hc (kg/cm 2 ), of heavy cloud (W hc >0.70 kg/m 2 ) is used to provide an additional indicator of scintillation, i.e.…”
Section: Van De Kamp Modelsmentioning
confidence: 99%